Termites and Global Warming - a Review - Thakur, R. K.; Hooda, N.; Jeeva, V. (Indian Forester, 2003)
Methane has been considered to be an important greenhouse gas (GHG) contributing significantly to global warming. Termites have been proved to be a most prominent source of abiogenic methane emission, though considerable uncertainty exists regarding the true estimates of methane emission. Significant studies are available on diversity, social structure, physiology and ecology, still termites as source of methane contributing to the sources of atmospheric greenhouse gas is yet to be explored in India. An attempt has been made to focus the importance of termites and their global contribution in GHG and need for detailed study in India for abatement oft rmites to reduce the GHG emission from termite source, as termites also to some extent contribute to land degradation and have serious implications for desertification.